FLOW-INJECTION SPECTROMETRIC DETERMINATION OF SODIUM DICLOFENAC IN PHARMACEUTICAL FORMULATIONS - E. F. Silva; P. R. B. Gomes; R. N. Fernandes; W. S. Lyra (Journal of the Chilean Chemical Society, 2018)
A flow-injection spectrometric method for determination of sodium diclofenac in pharmaceutical formulations was developed on this work. Sodium diclofenac solutions were injected into a stream of deionized water that reacted with potassium permanganate on acid medium producing Mn2+ ions whose exhibit maximum absorbance at 450 nm. The methodology used optimize experimental parameters was 33 factorial design and response surface. The proposed method obeyed the Beer’s Law over the range 25-160 mg L-1, applied in tablets and ampoules samples. Results were compare with the reference method. It was verified at the 95% confidence level, through paired t-test application – there is no statistic difference between them. The detection limit was valued in 2.6 mg L-1, relative standard deviation for 10 consecutive injections was 1.5% (100.0 mg L-1 sodium diclofenac solution) and the sample throughput was 80 samples h-1. Regarding optimization of operational conditions, the FIA spectrometric method presented analytical performance as good as other elaborated flow analyzers. Offers a simple and inexpensive way to this drug indirect determination aiming quality control on pharmaceutical industry’s assembly line. However, it can not be used for adulteration screening analysis due to non-selectivity and non-specificity of redox reactions.